2020
DOI: 10.2147/copd.s239841
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effectiveness and Economic Evaluation of Hospital-Outreach Pulmonary Rehabilitation for Patients with Chronic Obstructive Pulmonary Disease</p>

Abstract: Objective: Hospital-outreach pulmonary rehabilitation (PR) can improve health status and reduce health-care utilization by patients with chronic obstructive pulmonary disease (COPD). However, its long-term effects and costs versus benefits are still not clear. This study was conducted to develop, deliver, and evaluate the effects and monetary savings of a hospital-outreach PR program for patients with COPD. Methods: A randomized controlled trial was conducted. Patients with COPD (n=208) were randomly assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…Two studies that examined smoking interventions delivered during PR were ultimately not included in the main review: one study enrolled current smokers with and with no COPD and no subgroup analysis focused on patients with COPD, 12 and the second study did not report smoking abstinence rates. 43 Research in this area would be helpful to providers developing or refining PR programs to meet the diverse needs of patients. Finally, although this study provides a detailed, narrative review of smoking interventions for patients with COPD with discussion on how such interventions may be incorporated into PR, no quantitative methods were used to evaluate aggregated effects of intervention, examine possible moderators, or assess study quality as such efforts have been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies that examined smoking interventions delivered during PR were ultimately not included in the main review: one study enrolled current smokers with and with no COPD and no subgroup analysis focused on patients with COPD, 12 and the second study did not report smoking abstinence rates. 43 Research in this area would be helpful to providers developing or refining PR programs to meet the diverse needs of patients. Finally, although this study provides a detailed, narrative review of smoking interventions for patients with COPD with discussion on how such interventions may be incorporated into PR, no quantitative methods were used to evaluate aggregated effects of intervention, examine possible moderators, or assess study quality as such efforts have been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…As noted previously, none of the studies included in this review examined smoking cessation interventions delivered within the context of PR. Two studies that examined smoking interventions delivered during PR were ultimately not included in the main review: one study enrolled current smokers with and with no COPD and no subgroup analysis focused on patients with COPD,12 and the second study did not report smoking abstinence rates 43. Research in this area would be helpful to providers developing or refining PR programs to meet the diverse needs of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 32 studies met all of the eligibility criteria and were included in this meta‐analysis (Bernocchi et al, 2018; Cameron‐Tucker et al, 2016; Chatwin et al, 2016; Chen et al, 2014, 2021; Demeyer et al, 2017; Jehn et al, 2013; Jiménez‐Reguera et al, 2020; Kessler et al, 2018; Lahham et al, 2020; Li et al, 2014, 2018; Ma, 2019; McDowell et al, 2015; Mínguez Clemente et al, 2020; Park et al, 2020; Pinnock et al, 2013; Rixon et al, 2017; Steele et al, 2008; Tsai et al, 2017; Tupper et al, 2018; Vasilopoulou et al, 2017; Vianello et al, 2016; Vorrink et al, 2016; Walker et al, 2018; Wang et al, 2017; Wang, Guo, et al, 2021; Wang, Di, et al, 2021; Xing et al, 2021; Yan et al, 2018; Ye et al, 2019; Zhang et al, 2020). A flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…All relevant data were documented in the electronic health records to allow the administrators and patients to refer to relevant information using the internet (Wang et al, 2017). In 15 studies, patients in the intervention groups received multicomponent telehealth, including telerehabilitation, telemonitoring, and self‐management programmes (Chen et al, 2014, 2021; Demeyer et al, 2017; Jiménez‐Reguera et al, 2020; Kessler et al, 2018; Lahham et al, 2020; Ma, 2019; Park et al, 2020; Vorrink et al, 2016; Wang, Di, et al, 2021; Wang, Guo, et al, 2021; Xing et al, 2021; Yan et al, 2018; Ye et al, 2019; Zhang et al, 2020). The duration of home‐based telehealth interventions ranged from 8 weeks to 24 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation